2013
DOI: 10.1242/jeb.083543
|View full text |Cite
|
Sign up to set email alerts
|

A magnetic pulse does not affect homing pigeon navigation: a GPS tracking experiment

Abstract: SUMMARYThe cues by which homing pigeons are able to return to a home loft after displacement to unfamiliar release sites remain debated. A number of experiments in which migratory birds have been treated with a magnetic pulse have produced a disruption in their orientation, which argues that a ferrimagnetic sense is used for navigation in birds. One previous experiment has also indicated an effect of magnetic pulses on homing pigeon navigation, although with inconsistent results. Previous studies have shown th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Furthermore, magnetic pulse treatments under sunny conditions shifted the initial orientation direction of homing pigeons, thus providing further indication of the possible existence of a magnetic map (Beason et al, 1997). It should be noted though that such a pulse effect was not replicated in a recent study with GPS-tracked homing pigeons (Holland et al, 2013), which found no evidence of impairment of either initial orientation or navigation performance. Furthermore, there is also considerable evidence, which is not necessarily mutually exclusive to the possibility of the existence of a magnetic map, that homing pigeons use odours in the atmosphere at least at some locations on Earth to determine their position (for reviews, see Papi, 1992;Wallraff, 2004;Wallraff, 2006).…”
Section: Research Articlementioning
confidence: 86%
“…Furthermore, magnetic pulse treatments under sunny conditions shifted the initial orientation direction of homing pigeons, thus providing further indication of the possible existence of a magnetic map (Beason et al, 1997). It should be noted though that such a pulse effect was not replicated in a recent study with GPS-tracked homing pigeons (Holland et al, 2013), which found no evidence of impairment of either initial orientation or navigation performance. Furthermore, there is also considerable evidence, which is not necessarily mutually exclusive to the possibility of the existence of a magnetic map, that homing pigeons use odours in the atmosphere at least at some locations on Earth to determine their position (for reviews, see Papi, 1992;Wallraff, 2004;Wallraff, 2006).…”
Section: Research Articlementioning
confidence: 86%
“…While there has been great effort in attempting to understand the physiological basis of magnetite-based magnetoreception 15 , outside the laboratory a number of experiments, particularly those reporting tracking data, have not provided support for its role in the navigational map 10 14 17 32 33 34 35 36 37 . In contrast, the olfactory sense, long neglected in avian species, is increasingly demonstrated to be important in birds’ biology 38 including navigation.…”
Section: Discussionmentioning
confidence: 99%
“…The response to the pulse was restricted to experienced migrants that navigate towards an already familiar goal, whereas young birds on their first migration that fly innate courses were not affected [92]. This finding and the observation that homing pigeons treated with such a pulse deviated from untreated controls at some (but not all) sites in greater distances from home [93,94] indicate that the pulse affects a receptor that provides birds with a magnetic component of the navigational ‘map’ (see also [95]). Apparently, the pulse changes the course to be pursued, while the magnetic inclination compass remains unaffected [92,96].…”
Section: Magnetic ‘Map’ Components: Magnetite-based Receptors?mentioning
confidence: 99%